Case Report: Cannabidiol-Induced Skin Rash: A Case Series and Key Recommendations - Souza, José Diogo S.; Fassoni-Ribeiro, Maíra; Batista, Rayssa Miranda; Ushirohira, Juliana Mayumi; Zuardi, Antonio W.; Guimarães, Francisco S.; Campos, Alline C.; Osório, Flávia de Lima; Elias, Daniel; Souza, Cacilda S.; Fassoni, AndRea A.; Hallak, Jaime E. C.; et al. (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD) is a nonpsychotomimetic constituent of the Cannabis plant, with potential therapeutic properties for many physical and neuropsychiatric conditions. Isolated CBD has been suggested to have favorable safety and tolerability profile. Although CBD-related rash is described, few case reports are well documented in the literature, and usually, CBD was used concomitantly with other medications. Thus, we report four females who presented a skin rash after ongoing CBD use. Other causes of these skin rashes were ruled out after conducting an extensive viral and serological detection panel, and three patients had their lesions biopsied. Two patients were re-exposed to the vehicle (MCT) without developing a new skin rash. Therefore, clinicians must be aware of this potential adverse effect of CBD use.